Knowledge possessed and procedures applied by nursing personnel in relation to the care and handling of central venous catheters - Zerrizuela , Marcela Fabiana; Lara , Walter A. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: It was estimated that 8% of hospitalized patients will require a Central Venous Catheter (CVC), which implies risks of mechanical and infectious complications if not properly used. This study aimed to describe the knowledge and procedures of nursing staff in the management of patients with CVC. The research was developed in a public hospital in Rosario between August and September 2022. Methods: A quantitative methodological approach was used, with a non-experimental, descriptive and cross-sectional design. The population studied included nurses from a public hospital, and the sample consisted of 21 Nursing Technicians and one Bachelor working in intermediate care. The majority were women (77.27%), with an average age of 37 years. Data collection consisted of surveys to assess knowledge and direct observation of CVC management and healing procedures. Results: The nurses’ knowledge of biosafety and CVC maintenance was assessed as average, while that related to alarm patterns, risks and complications was lower. In the procedures observed, post-cure activities showed a high performance, highlighting the correct disposal of waste, hand washing and records. The pre-healing steps obtained acceptable results, but weaknesses were identified in the manipulation of lumens and connections. Actions during healing showed the lowest performance, although in general, the procedures exceeded the levels of knowledge evaluated. Conclusions: The study evidenced limited nursing staff knowledge in critical areas related to CVCs, which could increase the risk of complications. However, the procedures observed were acceptable, with strengths in the post-healing stages. Areas for improvement were identified, especially in actions during healing and device manipulation, suggesting the need for specific trainings to optimize the care of CVC patients